Estudo comparativo dos romances Galantes Memórias e Admiráveis Aventuras do Virtuoso Conselheiro Gomes, o Chalaça e Memórias Póstumas de Brás Cubas - Corrêa, Odilon Rosa (2009)
This work aims to compare the novels Galantes Memórias e Admiráveis Aventuras do Virtuoso Conselheiro Gomes, O Chalaça, from José Roberto Torero, and Memórias Póstumas de Brás Cubas, from Machado de Assis, focusing on the approach each autho r has to the narrative elements that concoct both novels, including the narrator. Our analysis of Torero´s novel also shows its intertextuality with Memórias Póstumas, Lazarillo de Tormes and the Holy Bible and also the use of daily expressions. Galantes Memórias is shown as a picaresque novel, in accordance with the original characteristics of this genre in Spain.